Teaching Narrative Paragraphs Using Authentic Materials: An Alternative - Susilowati, Meinarni (ULUL ALBAB Jurnal Studi Islam, 2001)
In general, teaching writing skills always takes a long time to arrive at the specified goals. Judging from the writing process, these skills involve various aspects of other languages so that they are often regarded as the most difficult language skills to be mastered. This article focuses on providing alternatives to teaching writing at the university level by utilizing authentic material. The lecturers can take advantage of other lecture material (novels, short stories or other texts) as the initial material for developing writing skills. Thus, to apply the information offered in this paper, a collaboration between lecturers is absolutely necessary.